2016
DOI: 10.4103/1596-3519.188896
|View full text |Cite
|
Sign up to set email alerts
|

Establishing in-hospital geriatrics services in Africa: Insights from the University of Benin Teaching Hospital geriatrics project

Abstract: Background:Unawareness of the peculiar healthcare needs of the elderly and resource constraints may be some reasons why until recently, Nigerian hospitals have not been equipped with the human and infrastructural resources required to meet older adults’ special healthcare needs. There is paucity of specialized health services for the elderly in Africa. Nigeria, with a population of over 170 million, did not have any healthcare facility with dedicated services for the elderly until 2012. The University of Benin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The Geriatrics Unit in University of Benin Teaching Hospital (UBTH) in Nigeria was established in an effort to provide quality healthcare to older persons with co-morbidities, using the Acute Care for Elders (ACE) model [5] . The service review reported in this paper is formative and was designed to assess the extent to which the initiative of setting up the unit had achieved the purpose; to disseminate lessons learned and make adjustments to the structures and processes, with a few to improving clinical outcomes [7] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Geriatrics Unit in University of Benin Teaching Hospital (UBTH) in Nigeria was established in an effort to provide quality healthcare to older persons with co-morbidities, using the Acute Care for Elders (ACE) model [5] . The service review reported in this paper is formative and was designed to assess the extent to which the initiative of setting up the unit had achieved the purpose; to disseminate lessons learned and make adjustments to the structures and processes, with a few to improving clinical outcomes [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Admissions were capped at a maximum in-patient number of 15 because of challenges with increasing the nursing and supporting the workforce. Criteria for admission included age equal to, or greater than 60 years and multiple medical (and other) conditions [5] . Documentation of regarding bed occupancy and bed stays, transfers in and out, discharges and deaths are routinely done by the geriatric nursing staff.…”
Section: Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…15 This rapid increase in the elderly population is also accompanied by a preponderance of non-communicable diseases in Nigeria 16 ; hence, the gaining momentum of geriatric/ gerontological practice in Nigeria is timely. 13,14 With the growing awareness of specialist care for older people in Nigeria, and recent interest by the Nigerian government to establish regional geriatric centres for clinical care, understanding the collaborative disciplinary experiences of HCPs working in a geriatric unit in a tertiary health institution is warranted. Due to resource constraints and other factors, we decided to explore the HCPs' perspective of the transdisciplinary approach in one centre in Nigeria, for several reasons.…”
Section: Introductionmentioning
confidence: 99%